When Wide Scope Is not Enough: Scope and Topicality of Discourse Referents - Barberà, Gemma (Proceedings of the Amsterdam Colloquium, 2011)
This paper analyses the semantic attributes discourse referents in Catalan Sign Language may have in order to have a corresponding location established in sign space. It is argued that a combination of scope and topicality is required when analysing the correlation between the introduction of entities into the discourse and assigning a spatial location.